Quantitative determination of carvedilol in human plasma by high-performance liquid chromatography using fluorescence detection - Nguyen, Dang Thuy Anh; Nguyen, Huu Tien (Tạp chí Y Dược Huế, 2024)
Background: Carvedilol is a pharmaceutical substance listed in the “Regulatory requirements of bioequivalence study reports for generic drugs containing APIs upon applying for marketing authorization”. Therefore, a simple method for quantifying carvedilol in human plasma is desirable. Objectives: This study aims to develop an HPLC method for quantitation of carvedilol in human plasma. Materials and method: The blank human plasma was spiked with carvedilol standard. After optimizing the process, the method was validated according to the guidelines for the validation of bioanalytical methods of US-FDA and EMA. Results: Carvedilol and metoprolol as internal standard were extracted from plasma by protein precipitation technique with acetonitrile. Plasma samples were eluted through a Zorbax Eclipse XDB-C8 (5 μm; 4.6 x 150 mm) column with an isocratic mobile phase consisting of 0.1% trifluoroacetic acid in water, acetonitrile, and methanol (60:20:20; v/v/v). The analytical method met the criteria according to the US-FDA and EMA guidelines for the bioanalytical method validation. Conclusion: The method can be applied to determine carvedilol in biological fluid for pharmacokinetic research and bioequivalence assessment.